2014
DOI: 10.5507/bp.2013.047
|View full text |Cite
|
Sign up to set email alerts
|

Neurosarcoidosis: Two case reports with multiple cranial nerve involvement and review of the literature

Abstract: aBackground. Involvement of the central nervous system is registered in a relatively small number of patients with sarcoidosis. In this article we present two cases with various neurological symptoms that fulfill criteria for neurosarcoidosis (NS). In addition, we review the literature on NS with special attention to isolated cranial nerve involvement. Methods and Results. First patient: Neurological examination identified multiple cranial neuropathy, moderate rightsided hemiparesis, polyradiculoneuritis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
1
7
0
1
Order By: Relevance
“…Several potentially neuroprotective agents function to upregulate gene transcription at the onset of brain ischemia, which may be an effective approach for limiting brain tissue damage (25). Studies on the mechanisms of cranial nerve involvement have shown that the serotonin systematic signaling pathway shows high correlation with the initiation, development, treatment and prognosis of cranial nerve involvement (26,27). In addition, an increasing number of studies have reported that the overexpression of histamine in the cerebrospinal fluid is a potential therapeutic target in patients with cranial nerve involvement and has been found be important in the pathogenesis of cranial nerve involvement (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Several potentially neuroprotective agents function to upregulate gene transcription at the onset of brain ischemia, which may be an effective approach for limiting brain tissue damage (25). Studies on the mechanisms of cranial nerve involvement have shown that the serotonin systematic signaling pathway shows high correlation with the initiation, development, treatment and prognosis of cranial nerve involvement (26,27). In addition, an increasing number of studies have reported that the overexpression of histamine in the cerebrospinal fluid is a potential therapeutic target in patients with cranial nerve involvement and has been found be important in the pathogenesis of cranial nerve involvement (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of the CNS, referred to as neurosarcoidosis (NS), occurs in only 5–15% of cases [ 14 , 22 ] with cranial neuropathies as the most frequent neurological manifestation [ 12 , 23 ]. Neuro-ophthalmic sarcoidosis is a specific subset of NS of unknown frequency that involves the afferent and efferent visual systems [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar puncture in sarcoidosis may demonstrate an elevated CSF protein and a mild-to-moderate pleocytosis with lymphocytic predominance or may be normal in a third of patients [ 9 , 10 ]. Decreased glucose levels may occur in one-fifth of patients [ 10 ]. Our patient's CSF showed lymphocytic predominance with normal protein.…”
Section: Discussionmentioning
confidence: 99%